A scale for measuring relative proximity of transactional distance. Issue 1 (2nd January 2022) - Paul, Ravi C.; Swart, William; MacLeod, Kenneth R.
Abstract: Relative proximity theory contributes to the concept of distance in distance education by defining how far a current learning environment is from an ideal learning environment. As in Moore's (1993 ) theory of transactional distance, it defines distance as a psychosocial phenomenon but provides specificity to Moore's seminal theory for learning at a distance by providing a specific answer to the question "How close are we?" in our continual journey to provide better learning environments for our students and teachers. This paper reports on our development of a statistically valid and reliable scale of relative proximity of transactional distance to measure the remaining distance to ideal. The scale adapts and extends the work by Zhang (2003 ), Paul et al. (2015 ), and Weidlich and Bastiaens (2018 ) and, for the first time, explicitly accounts for differences due to gender and mode of delivery.